From the "planning euphoria" to the "bitter economic truth": The transmission of economic ideas into German labour market policies in the 1960s and 2000s - Stephan Pühringer; Markus Griesser (Cusanus Hochschule, Institut für Ökonomie und Institut für Philosophie, 2017)
This paper compares the interconnections between dominant economic thought and processes of policy-making in the area of labour market reforms in Germany in the late 1960s and the early 2000s. The transition in labour market policies in this period could be described as a change from an active to an activating approach. At the level of economic discourse these policy changes correspond to a paradigm shift from Keynesian to neoclassical/neoliberal economic thought. We investigated these changes by focussing on two distinct reforms of labour market policies and carried out a critical discourse analysis of the relevant public and academic discourse of economists. We find that the paradigm shift in economic thought was accompanied by a shift in economists' discourses on labour market policy issues.
Keywords: A11; B21; B22; B52; J53; J41; J88; 330; critical discourse analysis; political power of economic ideas; labour market policy reforms; economic expert discourse